Chronology of Terrestrial Den Use by Polar Bears in Western Hudson Bay as Indicated by Tree Growth Anomalies - Scott, Peter A.; Stirling, Ian (ARCTIC, 2002)
In a large polar bear denning area inland from the coast of western Hudson Bay south of Churchill, Manitoba, previous denning activity was determined by examining tree growth anomalies in the black spruce (Picea mariana) around and above den sites. A concentrated sample of dens was examined at each of three lakes, and 14 additional den sites were sampled individually on nine lakes and streams, for a total of 31 den sites. Trees sampled at these den sites ranged in age from 46 to 236 years (n = 83, mean = 136, SE ± 95.66). Some individual den sites dated back at least 200 years. Although some dens had been used for up to 29 years, most were used for only 12 years or less, presumably until melting permafrost caused their collapse. Half of the dens were reused two years after their initial use, but the probability of den reuse declined in subsequent years to about 0.25 after 10 years. During the 20th century, coincident with a reduction in hunting during 1920-53 and the subsequent abandonment of York Factory, there appears to have been an increase in den activity and an accompanying change in the pattern of denning activity. The rate of disturbance to the trees at dens correlated significantly to the number of polar bear hides traded at York Factory over the 1840-1935 period (r = 0.654; p < 0.005). During 1850-99, denning activity was greater at points more distant from the trading post at York Factory. In 1900-53, there was an overall increase in denning activity, which was greatest in denning areas nearer to York Factory (r = -0.872; p < 0.01). In 1954-93, the increase in denning activity continued, but varied with distance from the coast (r = -0.724; p < 0.05). Mark-recapture studies undertaken from 1970 to 2000 confirm that female polar bears in the western Hudson Bay population have a long-term fidelity to this specific area for maternity denning, and from this study it is evident that the population has used this denning area for several hundred years at least. Dans une vaste zone où sont établies ...